Zero Point Energy - Adhikari, Krishna Raj (Himalayan Physics, 2011)
Zero point Energy/ zero point fields are not the new issue in the arena of physics but we feel new. Here, I am not going to set up a model to calculate zero point energy in particular case but collect some ideas and give definition of zero point energy, based on earlier brief attempts and present two ways of getting zero point energy in nature and some calculated result of zero point energy in some special cases. These things provide some ideas about zero point energy and substantiate the entity of zero point fluctuations and zero point energy in vacuum even at absolute zero. The Himalayan Physics Vol.1, No.1, May, 2010 Page: 67-68 Uploaded Date: 28 July, 2011